Whipple's pancreaticoduodenectomy in pediatric patients: An experience from a tertiary care center - Abhimanyu Varshney; Anjan Kumar Dhua; Vishesh Jain; Sandeep Agarwala; Veereshwar Bhatnagar (Wolters Kluwer Medknow Publications, 2018)
Purpose: Whipple's pancreaticoduodenectomy (WPD) is rarely required in children. However, WPD is the only option with pathologies involving the head of the pancreas requiring surgical excision. The objective of our study was to review our experience with WPD performed on children. Materials and Methods: A retrospective analysis of case records was conducted on all patients <18 years of age, who underwent WPD at our center over the last 20 years. Data regarding demographics, signs, and symptoms at presentation, diagnostic imaging and procedures, pathologic reports, surgical and medical treatment, and follow-up were collected to study the indications and safety and outcomes of WPD in children. Results: Five patients had been planned for a WPD during the study (1995-2015); but in one patient, the procedure was abandoned, the rest four patients formed the study group. Male to female ratio was 3:1. Median age at the time of surgery was 9 years (11 months-12 years). The most common presentation was obstructive jaundice (50%, 2/4). Radiological imaging was able to accurately predict the surgical procedure required in all except one case. The mean operating time was 205 min (180-240 min). There were no intraoperative complications. The mean intraoperative blood loss was 85 mL (20-150 mL). The youngest patient requiring WPD was an 11-month-old child. Oral feeding was established by the 7th postoperative day (range 5-7 days) in all cases. There were no cases of anastomotic leak or pancreatic or jejunal fistulae. One patient developed features of subacute intestinal obstruction after discharge and required re-exploration. There was no intra- or post-operative mortality. Conclusion: WPD is safe and efficacious procedure in a selected group of children. The overall efficacy of surgical treatment combined with the relatively low severity of complications leads us to recommend WPD in children when indicated.